Aspek Normatif dalam Pertanggungjawaban Pidana Anak - Putra Riskiawan; Imam Mujtahid Azzuhdi (Laskar Karya, 2024)
This research discusses normative aspects related to children's criminal responsibility in the legal system. Highlighting the ethical foundations and values ​​of justice, this article explores the principles that should guide the handling of criminal cases involving children. By reviewing related regulations and norms, this journal explores how criminal law can provide protection and guidance that is appropriate to children's developmental stages and human rights. This discussion covers normative aspects related to punishment, rehabilitation and social integration of children involved in criminal acts. The conclusions of this journal provide in-depth insight into the challenges and perspectives of juvenile criminal law in an effort to create a legal system oriented towards child welfare and justice based on internationally recognized normative values.